Notable differences in gene expression between injured turbot (Scophthalmus maximus) and brill (Scophthalmus rhombus) skin - Estêvão, João Luis Correia (2015)
Dissertação de mestrado, Engenharia Biológica, Faculdade de Ciências e Tecnologia, Universidade do Algarve, 2015 The skin, the largest organ of fish’s body and first barrier against external agents, plays a crucial role against environmental aggressions and is decisive in communication between individuals. Cutaneous lesions are common in fish and may result in an open door for infectious agents and originate osmotic stress, which can be life threatening for the animal. Turbot (Scophthalmus maximus) and brill (Scophthalmus rhombus) are two closely related congeneric species with striking differences in their skin, since turbot presents tubercles instead of the scales found in brill. In this work, gene expression analyses were performed in order to analyze the genetic differences in the skin response between the two species. Skin scraping areas (72 h after injury) from three biological replicates of each species were compared with normal skin areas from the same individuals. A previously reported 4x44k Agilent turbot microarray was employed, after evaluating its suitability by comparison of the base sequence of common genes using bioinformatics. Skin-related genes from previous studies (1564 sequences) were taken as a reference to screen the turbot database and the oligo-probes in the microarray. Among them, 584 (~37%) were present in the turbot database (e-value < 9x10-20) and 326 (~21%) contained oligo-probe in the microarray, a notable result since the microarray was especially enriched with immune-related organs. Genes with a significant fluorescent signal in the microarray (>200 fluorescence units) were identified in each (turbot: 15,739; brill: 12,393) and in both species (10,065). Among them, 1750 differentially expressed genes (t-test p-value p<0.005; log2 ratio <-2 and >2) were detected in brill, 1461 in turbot, and 885 showed differences between species, respectively. These results strongly suggest: 1) the turbot microarray is suitable for gene expression analysis in brill, and 2) a ...